Local Strain Engineering of Two-Dimensional Transition Metal Dichalcogenides Towards Quantum Emitters - Ruoqi Ai; Ximin Cui; Yang Li; Xiaolu Zhuo (Nano-Micro Letters)
Highlights Methods for creating the local deformation in two-dimensional transition metal dichalcogenides (2D TMDCs) are introduced. Modulations of local strain on their optical properties and excitonic behaviors are discussed. Quantum emitters based on strained 2D TMDCs and other applications are presented.